Vanishing Ice : Glaciers, Ice Sheets, and Rising Seas - Gornitz, Vivien (Columbia University Press, 2019)
The Arctic is thawing. In summer, cruise ships sail through the once ice-clogged Northwest Passage, lakes form on top of the Greenland Ice Sheet, and polar bears swim farther and farther in search of waning ice floes. At the opposite end of the world, floating Antarctic ice shelves are shrinking. Mountain glaciers are in retreat worldwide, unleashing flash floods and avalanches. We are on thin ice-and with melting permafrost's potential to let loose still more greenhouse gases, these changes may be just the beginning.Vanishing Ice is a powerful depiction of the dramatic transformation of the cryosphere-the world of ice and snow-and its consequences for the human world. Delving into the major components of the cryosphere, including ice sheets, valley glaciers, permafrost, and floating ice, Vivien Gornitz gives an up-to-date explanation of key current trends in the decline of ice mass. Drawing on a long-term perspective gained by examining changes in the cryosphere and corresponding variations in sea level over millions of years, she demonstrates the link between thawing ice and sea-level rise to point to the social and economic challenges on the horizon. Gornitz highlights the widespread repercussions of ice loss, which will affect countless people far removed from frozen regions, to explain why the big meltdown matters to us all. Written for all readers and students interested in the science of our changing climate, Vanishing Ice is an accessible and lucid warning of the coming thaw.